Reg4, triggering a positive feedback regulatory circuit, promotes peritoneal metastasis of gastric cancer - He-Xiao Wang (临床与病理杂志; 卷 35, 编号 1 (6 2015), 2026)
Objective: To establish a positive feedback circuit triggered by Reg4 and investigates its significance in peritoneal metastasis of gastric cancer. Methods: Reg4 expression was detected in gastric cancer samples by immunohistochemistry staining. Reg4 overexpressed and knocked down cells were used to investigate its biological function. Activation of EGFR pathway and promotion of Reg4 were evaluated upon EGFR ligand stimulation. Mass spectrometry was performed to identify Reg4 receptor. ADAM phosphorylation and EGFR ligand shedding was detected after upstream manipulation. Possible downstream effectors were investigated by PCR array. Results: Expression of Reg4 was higher in gastric cancer tissues. Reg4 enhanced prometastatic abilities of gastric cancer cells. EGFR ligand was able to induce Reg4 expression through sequential EGFR pathway activation. Reg4 receptor was identified by mass spectrometry. ADAM phosphorylation and EGFR ligand shedding were enhanced after Reg4 overexpression. PCR array showed several promising downstream effectors. Conclusion: Reg4 is able to trigger a positive feedback regulatory circuit that promotes peritoneal metastasis of gastric cancer.